Cango Lyec (Healing the Elephant): HIV incidence in post-conflict Northern Uganda - Katamba, Achilles; Ogwang, Martin D.; Zamar, David S.; Muyinda, Herbert; Oneka, Alex; Atim, Stella; Jongbloed, Kate; Malamba, Samuel S.; Odongping, Tonny; Friedman, Anton J.; Spittal, Patricia M.; Sewankambo, Nelson K.; et al. (EClinicalMedicine, 2020)
Civil war in Northern Uganda resulted in widespread atrocities, human rights violations, and death, and caused millions to flee to internally displaced persons camps. War-related traumas combined with difficulties accessing HIV prevention and health services has led to extreme HIV-related vulnerability among conflict-affected people who survived the war. Objectives were to (1) determine HIV incidence among conflict-affected people in Northern Uganda and (2) identify vulnerabilities associated with HIV infection. Methods: The Cango Lyec (Healing the Elephant) Project is a prospective cohort involving conflict-affected populations in three districts in Northern Uganda. In 2011, eight randomly selected communities were mapped, and a census was conducted. Consenting participants aged 13 49 years were followed over three rounds of follow-up. Longitudinal data collected included war-related experiences, sexual vulnerabilities, and sociodemographics. Blood samples were tested for HIV-1 at baseline and each 12-month follow-up. Multivariable Cox proportional hazard models determined factors associated with HIV incidence. Findings: Overall, 1920 baseline HIV-negative participants with at least one follow-up contributed 3877 person-years (py) for analysis. Thirty-nine (23 female, 16 male) participants contracted HIV during follow-up. Age- and gender-standardised HIV incidence rate was 102 per 1000py (95%CI: 72-140). Stratified by sex, the age-adjusted HIV incidence was 110 per 1000py (95%CI: 69-166) among women and 94 per 1000py (95%CI: 53-153) among men. Adjusting for confounders, factors associated with risk of HIV included: having been abducted (HR: 370; 95%CI: 187-734), experiencing 12 war-related traumatic events (HR: 291 95%CI: 128-660), suicide ideation (HR: 283; 95%CI: 100-803), having 2 sexual partners (HR: 468; 95%CI: 136-1605), inconsistent condom use (HR: 675; 95%CI: 249-1829), and self-reported genital ulcers (HR: 439; 95%CI: 204-945). Interpretation: Conflict-affected participants who had experienced abduction and multiple traumas during the war were at greater risk of HIV infection. Trauma-informed HIV prevention and treatment services, and culturally-safe mental health initiatives, are urgent for Northern Uganda
Keywords: HIV/AIDS; Conflict-affected people; HIV incidence; Trauma; Mental health